The Role of Waste Generation and Composition Data in Advancing Circular Economy Strategies in Indonesia - Atthaya Namira Yulianto, Khenza (International Journal of Educational Research & Social Sciences, 2026)
Rapid urbanization, population growth, and shifting consumption patterns have significantly increased municipal solid waste (MSW) generation in Indonesia, exposing structural inefficiencies in material use and post-consumption management under a predominantly linear economic model. National data indicate that waste generation has reached approximately 0.833 kg per capita per day, with urban waste volumes increasing substantially between 2020 and 2024 and concentrated primarily in densely populated regions such as Java, Sumatra, and Borneo. Waste composition analysis further reveals that organic waste remains the dominant fraction at nearly 40% of total municipal waste, followed by a rising plastic fraction approaching 20%, underscoring the need for data-driven circular economy strategies. This study employs a systematic review methodology, synthesizing peer-reviewed literature, governmental reports, and institutional documents to examine how waste generation and composition data can inform circular economy planning in Indonesia. The analysis integrates national waste statistics with evaluations of existing initiatives—including waste banks, Extended Producer Responsibility (EPR) schemes, refuse-derived fuel (RDF) production, composting programs, anaerobic digestion, and Black Soldier Fly (BSF) bioconversion—and compares them with international best practices suited to similar waste profiles. The findings indicate that although Indonesia has formally adopted circular economy principles and implemented various recovery-oriented programs, their scale and integration remain insufficient relative to the dominant organic and plastic fractions. Organic waste presents significant potential for biological treatment pathways such as composting and anaerobic digestion, while increasing plastic waste necessitates stronger upstream product redesign and reverse logistics systems. The study concludes that integrating reliable waste generation and composition data into policy formulation and technology deployment is essential for advancing evidence-based, scalable, and context-sensitive circular economy strategies capable of reducing landfill dependency and enhancing resource efficiency in Indonesia.